Morfología bucofaríngea y hábitos alimentarios de Micropogonias furnieri (Pisces: Sciaenidae) en la costa norte del Estado Sucre, Venezuela - Ruiz, Lilia J (2001)
Morphology of the mandibular and pharyngeal region, and the feeding habits of Micropogonias furnieri were examined in 256 male and female specimens, between 28.7 and 54.3 cm total length, collected around Morro Puerto Santo, in northeast Sucre State, Venezuela (10º 45’00” N- 63º 8’0” W), from May 1989 to April 1990. Micropogonias furnieri has a small ventral mouth; protrusible premaxillary and dentary; first branchial arches with 21 to 27 gill rakers, generally 24 to 25; and 7 to 11 pyloric caecae. The index of vacuity was low, with mean value of 7.00 %. The mean intestinal index was 0.72, indicative of carnivorous species. Analysis of frequency of occurrence, indicates preference for crustaceans (45.70 %), mainly crabs (34.90 %), followed by polychaetes (28.00 %), fishes (11.41 %) and occasionally mollusks and echinoderms (4.0 and 3.9 %, respectively). The diet of this species did not vary with sex.